2012
DOI: 10.17073/0368-0797-2012-11-28-31
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Action Circuit Design Impact on Wheel Steel Cast Metal

Abstract: Национальный исследовательский технологический университет «МИСиС» ВЛИЯНИЕ СХЕМЫ ДЕФОРМАЦИОННОГО ВОЗДЕЙСТВИЯ НА ЛИТОЙ МЕТАЛЛ КОЛЕСНОЙ СТАЛИФизико-механические и эксплуатационные свойства металлопродукции, получаемой обработкой металлов давлением, зависят от созданной структуры металла изделий, формирование которой определяется состоя-нием исходной структуры заготовки, схемой дефор-мирования (способа обработки металлов давлением), термомеханическими режимами процесса (величиной деформации, температурой начала и… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Previously studies have been performed for the effect of piercing billets with small drawing coefficients (μ ≈ 1.3) on cast wheel steel mechanical properties. It has been demonstrated that with insignificant reductions screw piercing provides an increase in steel ductility properties with resistance to impact loads [10][11][12]. On the basis of these studies for preparing especially thin-walled sleeves in a two-roll screw rolling mill it may be suggested that use of this process for manufacturing an original hollow billet provides preparation of wagon hollow axles in accordance with specifications laid down for this product.…”
mentioning
confidence: 99%
“…Previously studies have been performed for the effect of piercing billets with small drawing coefficients (μ ≈ 1.3) on cast wheel steel mechanical properties. It has been demonstrated that with insignificant reductions screw piercing provides an increase in steel ductility properties with resistance to impact loads [10][11][12]. On the basis of these studies for preparing especially thin-walled sleeves in a two-roll screw rolling mill it may be suggested that use of this process for manufacturing an original hollow billet provides preparation of wagon hollow axles in accordance with specifications laid down for this product.…”
mentioning
confidence: 99%